Study of Arteriovenous Fistula Cases in a Tertiary Care Hospital: A Descriptive Cross-sectional Study - Karmacharya, Robin Man (JNMA J Nepal Med Assoc, 2020)
INTRODUCTION: Arteriovenous fistulas are a preferred choice for hemodialysis access in chronic kidney disease patients. There is increased adoption of arteriovenous fistula creation in Nepal. Our objective is to study various arteriovenous fistulas that have been created in our center. METHODS: This is a descriptive cross-sectional study conducted in a tertiary care hospital including all cases of arteriovenous fistula creation from January 2018 to December 2019. We obtained the ethical clearance from the institutional review committee of Kathmandu University School of Medical sciences. Convenient sampling method was used. Detailed vascular mapping and color doppler ultrasonography was done in the bilateral upper limb as preoperative preparation and to choose a site for arteriovenous fistula creation. Data were entered into the Statistical Package for the Social Sciences version 20 for analysis. RESULTS: Among 50 patients, the most common location was brachiobasilic 20 (40%) patients followed by brachiocephalic 18 (36%), radiocephalic 11 (22%), and arteriovenous graft between the brachial artery and axillary vein 1 (2%). The mean duration of hospital stay was 1.44 days. Three (6%) patients required re-intervention, all within 24 hours. Two (4%) patients had a failure of arteriovenous fistula requiring the creation of a new arteriovenous fistula. CONCLUSIONS: Brachiobasilic was the most common location for arteriovenous fistula creation. Reintervention was not common.